Cache memory loaclity optimization for implementation of computer vision and image processing algorithms - al-Marakbi, Ashraf (Journal of Al-Azhar University Engineering Sector, 2020)
سرعة الذاكرة تمثل واحدة من أهم المشكلات التي تواجه عملية تطوير أنظمة سريعة لمعالجة الصور والرؤية بالحاسب. إن سرعة الذاكرة تمثل عنق الزجاجة في تحقيق أداء جيد نظرا للفجوة الكبيرة بين سرعة الذاكرة وسرعة المعالج. الذاكرة المخبأة هي ذاكرة سريعة جدا ولكنها صغيرة ولا يمكنها تخزين جميع البيانات والتعليمات المطلوبة. في هذا البحث يتم عمل تحسين لخوازميات الرؤية بالحاسب ومعالجة الصور من أجل تحسين الأداء عن طريق زيادة استغلال أفضل للذاكرة المخبأة. هذه الأمثلة تزيد من التركيز المكاني والتركيز الوقتي لتحسين الأداء. الأمثلة المقترحة تم تطبيقها على العديد من عمليات معالجة الصور مثل تحويلات الوضوح ومرشحات الصور والتحويلات الهندسية والشبكات العصبية. إن تحليلات الوقت لهذه الأنظمة أثبتت تحسينات في السرعة تصل من 30% إلى 70% مقارنة بالطرق المباشرة لتنفيذ هذه الخوارزميات. One of the main problems in developing fast image processing and computer vision systems is the memory speed. memory speed represents the performance bottleneck due to the large gap between processor and memory speeds. cache memory is very fast, but it is small to store all required data and instructions. in this paper, image processing and computer vision algorithms are optimized to enhance performance by increasing the cache memory utilization. this optimization increases the spatial locality and temporal locality and improves the system performance. the proposed optimization is applied on a set of image processing operations such as image intensity transformation, image filtering, geometric transformation, and CNN. the time analysis of the systems has shown a speed improvement of 30% to 70% compared with direct algorithm implementation.